Strategi Pemasaran Anyaman Tikar Berbahan Baku Daun Lontar di Desa Lenteng Barat Kec Lenteng - Hajar Hajar; Syafiqur Rahman; Ahmad Mahfudz; Moh. Rifqi (STEI Kanjeng Sepuh Gresik Jawa Timur, 2021)
The lack of strategy in marketing woven mats made from palm leaf in West Lenteng Village is the cause of the decline in sales of woven mats made from lontar leaves. This research uses qualitative research with a descriptive approach. This type of research is field research, i.e. jumping directly into the research site. The location and time of the study took place in the western village began on September 3, 2021 which was sourced from primary data and Skunder Data. Data collection techniques are by observation, interview and documentation methods. Data analysis uses the miles and huberman model with three stages, namely data reduction, data presentation and conclusion.Marketing strategies used in woven mat marketing in West Lenteng Village use 4P: Products, Promotions, Prices and Locations The marketing of products carried out by mat craftsmen includes: a) the type of product in the form of woven mats made from lontar leaves. b) product development through a tighter and neater mat form that distinguishes with the production of other mats. c) Good mat quality prepared by the mat craftsmen selected by selection in order to produce a good mat. Marketing strategies against prices set by mat craftsmen are: a) Factors that affect the pricing of mat webbing are economic conditions, natural conditions, competition and costs. b) The purpose of pricing is optimization of increased operating profit. Marketing strategies to distributors carried out by woven mat craftsmen are: a) Direct distribution (where artisans woven mat-consumers) b) Indirect distribution, 1. Artisan-retailer-consumer 2. Artisan-agent-consumer 3. Artisan-agents-retailer-consumer. Marketing strategy for promotion carried out by mat craftsmen in the village of west lenteng is publicity relations: a). cooperation with the community b). Fellow craftsmen woven mat c). Person to person. This mat woven strategy prioritizes quality lontar leaf raw materials so as to produce strong and durable goods. And the different way of making it becomes a characteristic of woven from West Lenteng Village. The obstacles faced from the mat woven marketing strategy is that a place very far from the highway makes it difficult for consumers to reach it and only reach by collectors. The second obstacle is that marketing using publicity is the cause of weak introduction to public affairs.